Effects of prior antioxidant supplementation on quality of stored erythrocytes: vitamin C + vitamin E and vitamin C + N-acetylcysteine - Masannagari Pallavi; Vani Rajashekaraiah (European Journal of Translational and Clinical Medicine)
Background: The antioxidant status of donors may impact the quality of stored blood and its components. Therefore, oral antioxidant supplementation prior to blood donation could be a promising approach to improve the efficacy of stored erythrocytes. Materials and methods: Wistar rats (3 months old, n = 5/group) were categorized into controls, antioxidant group 1 (vitamin C and vitamin E, VC + VE group), antioxidant group 2 (vitamin C and N-acetylcysteine, VC + NAC group). Experimental rats were supplemented for 30 days. Erythrocytes were stored in additive solution (AS-7) for 42 days and analyzed at two-week intervals. Results: Hemoglobin increased on days 28 and 42 in both the antioxidant groups. Superoxide dismutase and catalase activities elevated during initial days and, glutathione peroxidase activity towards the end of storage in the antioxidant groups. Protein carbonyls and malondialdehyde levels decreased in the antioxidant groups. Glutathione levels increased on day 42 in VC + VE. Hemolysis was lower in the VC + VE group until day 28 and was similar in the VC + NAC group. Conclusion: VC + VE and VC + NAC supplements protected hemoglobin, blood proteins and lipids from oxidation and elevated antioxidant defenses. Therefore, prior supplementation augments the antioxidant status and quality of stored blood.